Flexibility enhancement with vibration: Acute and long-term - Sands, W. A.; McNeal, J. R.; Stone, M. H.; Russell, E. M.; Jemni, M. (Medicine & Science in Sports & Exercise, 2006)
Introduction: The most popular method of stretching is static stretching. Vibration may provide a means of enhancing range of motion beyond that of static stretching alone.